Approaches and mechanisms for increasing capacity and internal building radio coverage of mobile cellular networks - Pasarelski, Rosen (Yearbook Telecommunications, 2022)
The aim of the report is to study different approaches and mechanisms for increasing the capacity and internal building radio coverage of mobile cellular networks. Various methods for indoor radio coverage are presented by comparing and analyzing the proposed solutions. On the occasion of overcoming the limitation of external microcells, other differentiated approaches are proposed for direct increase of the internal building signal. The approach consists of implementing antennas and equipment directly inside the buildings. These indoor antennas and radio engineering is defined as a distributed antenna system. With the development of mobile cellular networks of the fourth 4G and the introduction of the fifth 5G generation increasingly began to rely on a new optimal and effective approach to improving internal radio coverage and capacity in buildings and premises of end users presented as home base stations or femtocells.